ISLAMIC EDUCATION LEARNING MODEL DURING COVID 19 PANDEMIC IN IMPROVING THE LEARNING OUTCOMES IN SMP NEGERI 3 CILEUNGSI - Ilyas Prasetyo; Undang Ruslan Wahyudin; Oyoh Bariyah (Fakultas Agama Islam Universitas Wiralodra, 2022)
This research aims to analyze the Islamic education learning model during Covid-19 pandemic at state Junior High Scool. This qualitative approach is done intensively, researchers participate in the field, record carefully, perform analysis, make. The type of research taken is field research that is research that collects data done by obtaining through investigation based on field. Data collection methods use observation, interview and documentation methods. the results showed that the researchers carried out at the State Junior High School 3 Cileungsi, that by giving assignments and the types of assignments used with steps for selecting good and not boring task materials suitable for students, the teacher would easily explain and students would be interested and pay attention and be actively involved in working on group assignments. Learning Islamic Religious Education by using the task method is less effective. The Learning Process of Islamic Religious Education During the Covid 19 Pandemic Period at the State Junior High School 3 Cileungsi was less effective due to the difficulty of learning via online, preventing students from understanding the learning process of Islamic religious education.